Gender Inequality in Health: Examining the Impact of Health Policy on Women’s Health Rights in Indonesia (Indonesian Health Justice Review, 2025)
Gender inequality in Indonesia has profound effects on women’s health rights, limiting their access to essential services such as maternal care, reproductive health, and gender-based violence support. This paper critically examines how health policies in Indonesia contribute to or mitigate these gender disparities, particularly in the context of maternal and reproductive health services. Through a review of national health policies, legal frameworks, and interviews with healthcare providers and women’s rights advocates, the study identifies key barriers women face in accessing adequate healthcare. Findings suggest that although progress has been made, women—especially those in rural and low-income areas—continue to experience restricted access to maternal care, contraceptive services, and safe childbirth options due to cultural norms, inadequate healthcare infrastructure, and lack of education. The paper argues that addressing gender inequality in health requires a systemic approach that includes policy reform, education, and the removal of legal barriers to women’s health rights. Recommendations include improving access to reproductive health services, strengthening policies around gender-based violence, and ensuring that health policies promote the autonomy and rights of women, particularly in marginalized communities.